Splenogonadal fusion: a case report of three cases and a literature review - Luo, Na; Xu, Qitao; Wang, Hao; Su, Jiahong; Li, Shoulin (Frontiers in Pediatrics, 2024)
Purpose This case report aims to enhance the understanding of clinical physicians regarding splenogonadal fusion (SGF) and to help them consider SGF as a differential diagnosis when testicular tumors are suspected, thus avoiding unnecessary orchiectomies. Methods We report three cases of SGF admitted to our hospital, one of which presented as a suspected testicular tumor. We also searched the literature on scrotal masses from the last 25 years and summarize the characteristics of cases of SGF manifesting as scrotal swelling combined with our cases. Results After conducting a thorough search, we found a total of 24 publications relevant to this case study, which included 25 testes. All lesions were located on the left side, and the average age of those affected was 20.22 years. Seven cases were of the continuous type. Three cases presented with pain, all of which were intratesticular masses. Thirty cases had a definite onset duration, ranging from 3 weeks to 10 years. Nine patients (36%) underwent orchiectomy, and one underwent partial orchiectomy. Conclusion It is crucial to identify SGF in the clinic. When a patient presents with scrotal swelling, diagnosing SGF preoperatively is challenging, and it should be considered when there is a long history of a stable testicular mass. An intraoperative frozen section should be performed if a testicular tumor is suspected to avoid unnecessary orchiectomy.